Perbandingan Kualitas Hidup Penderita Kanker Ovarium Epitelial yang Diberikan Kemoterapi Regimen Paclitaxel dan Carboplatin dengan Regimen Cyclophospamide, Adriamicyn dan Cisplatin di RSUP Dr. Sardjito - Ahyar, Ibnu; Taufiqurrachman, Irwan; Kusumanto, Ardhanu (JURNAL KESEHATAN REPRODUKSI, 2017)
Background: Epithelial ovarian cancer is the dominant type of ovarian cancer. Platinum and Taxane regiment has been proved to increase the survival rate of ovarian cancer patientsObjective: To compare the quality of life of ovarian cancer patients who got Paclitaxel and Carboplatin regiments with Cyclophosphamide, Adriamycin and Cisplatin regiments and risk factors which influence themMethod: The design of the study was retrospective cohort. The total subjects were 156 ovarian cancer patients who consisted of 79 patients with paclitaxel and carboplatin regiments and dan 77 patients who got cyclophospamide, adriamicyn dan cisplatin regiments in DR. Sardjito hospital, Yogyakarta. The quality of life was measured with EORTC QLQ-C30. The data distribution were tested with KolmogorovSmirnov and analysed with D Chi-Squaretest for categorical data and Mann-Whitney for continuous data. Multivariable Analysis was done with logistic regression.Result and Discussion: The bivariable analysis of ovarian cancer stage and the quality of life showed that early stage of ovarian cancer patients had quality of life 19,068 times higher than advance stage of ovarian cancer patients (RR 19,068; 95% CI 2,590-140,362). There were signicant differences in quality of life in ovarian cancer patients with low body mass index <18,5 compared to normal body mass index as well as the titer of tumor marker Ca125. Multivariable analysis showed that there was no significant difference in quality of life between ovarian cancer patients who got Paclitaxel plus Carboplatin and ovarian cancer patients who got Cyclophospamide, Adriamicyn plus Cisplatin.Conclusion: there was no significant difference in quality of life between ovarian cancer patients who got Paclitaxel plus Carboplatin and ovarian cancer patients who got Cyclophospamide, Adriamicyn plus Cisplatin in DR. Sardjito Hospital, Yogyakarta.Keywords: Quality of life, ovarian cancer, paclitaxel plus carboplatin regiment, cyclophospamide, adriamicyn plus cisplatin regiment.